BIODIESEL PRODUCTION FROM WASTE COOKING OIL BY USING ULTRASONIC TUBULAR REACTOR - E. Agustian; A. Praptijanto; D. Sebayang; A. Z. M. Rus; S. Hasan (Universitas Mercu Buana, 2016)
The aim of this research is to find an optimum of synthesis biodiesel from waste cooking oil (WCO) using ultrasonic tubular reactor. The experimental studies explored the variations in reaction time, molar ratio WCO to methanol (MeOH), amount of catalyst, frequency of ultrasonic and output power ultrasonic on the ester contents. Comparisons of type ultrasonic and also mechanical stirring method based on time reaction were investigated. The optimum results of biodiesel process is the reaction time of 5 minute, NaOH catalyst 1%wt of WCO, molar ratio WCO to MeOH of 1:6, frequency ultrasonic of 20 KHz and output power ultrasonic of 650 W. The reaction time reduced 12-24 times compared to both of method and the yield of ester contents was obtained at 96.54%wt.